The Global Alzheimer's Association Interactive Network. Issue 1 (25th August 2015) - Toga, Arthur W.; Neu, Scott C.; Bhatt, Priya; Crawford, Karen L.; Ashish, Naveen
Abstract: Introduction: The Global Alzheimer's Association Interactive Network (GAAIN) is consolidating the efforts of independent Alzheimer's disease data repositories around the world with the goals of revealing more insights into the causes of Alzheimer's disease, improving treatments, and designing preventative measures that delay the onset of physical symptoms. Methods: We developed a system for federating these repositories that is reliant on the tenets that (1) its participants require incentives to join, (2) joining the network is not disruptive to existing repository systems, and (3) the data ownership rights of its members are protected. Results: We are currently in various phases of recruitment with over 55 data repositories in North America, Europe, Asia, and Australia and can presently query >250, 000 subjects using GAAIN's search interfaces. Discussion: GAAIN's data sharing philosophy, which guided our architectural choices, is conducive to motivating membership in a voluntary data sharing network.